Advancements in Immunotherapeutic and Targeted Approaches for Bladder Cancer Treatment - Muhammad Ameen; Urooj Niaz; Saadat Hassan Hashmi; Yassar Hussain Patujo; Ahmed Sajjad; Ghulam Mujtaba (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Bladder cancer, an aggressive malignancy with high incidence and mortality worldwide, is a significant health risk, particularly in older men. The use of tobacco and exposure to occupational carcinogens are two significant risk factors. Bladder cancer is either categorized as non-muscle-invasive (NMIBC) or muscle-invasive (MIBC), with NMIBC being less severe but more prone to recurrence, and MIBC having a disastrous prognosis. Surgery, chemotherapy, and immunotherapy are the usual treatments, though outcomes for advanced disease remain poor. More recent advances in immunotherapy and targeted therapies, including immune checkpoint blockade and FGFR inhibitors, offer promising alternatives. Objective: To evaluate the safety and effectiveness of immunotherapy and targeted medicines in the treatment of bladder cancer, with a focus on reducing the disease’s progression and recurrence while enhancing patient outcomes overall. Duration and place of study: This study was conducted in Riphah International Hospital Islamabad from January 2023 to January 2025 Methodology: This research was conducted with 140 biopsy-proven bladder cancer patients aimed to explore immunotherapy, targeted therapy, and standard cisplatin-based treatment regarding efficacy and safety. The patients were divided into three arms: one got immunotherapy, another got targeted therapy, and the third got standard treatment. Recent systemic therapy for cancer was one of the exclusion criteria. Demographic data, clinical presentations, and results were collected and followed for 24 months using imaging, laboratory results, and ECOG status. Statistical testing with SPSS 24.0 employed t-tests, ANOVA, and chi-square tests with p<0.05 as the threshold for significance. Results: There were a total of 140 individuals who were a part of this study. The mean age calculated was 65 years. The males were in majority in the participants. Participants were divided into 3 groups and were treated with different therapies. The first group was treated with immunotherapy which had a total of 55 participants while the minority was in the group with standard care. Patients developed some adverse events out of which 30% cases reported small symptoms such as fatigue and nausea. Conclusion: Bladder cancer patients who are treated with immunotherapy and targeted therapy have improved survival rates and the ability to remove the tumour compared to those who are treated with conventional treatments.